THE EFFECT OF PERSON-ORGANIZATION FIT, JOB SATISFACTION, AND TRUST TOWARD HIGH SCHOOLS’ TEACHERS AFFECTIVE COMMITMENT - Hamidah Hamidah; Mukhnery Mukhtar; Neti Karniati (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This study aims to determine the effect of a positive direct independent variables such as: person-organization fit, job satisfaction and trust in the dependent variable is the affective commitment high schools’ teachers in Depok. Studies have been conducted on senior high school teachers in Depok. The method used was a survey with data analysis techniques using path analysis. Respondents are 194 of the total 376 senior high schools’ teachers in Depok. They were selected by random sampling. The results of the study are as follows: (1) there was a direct effect of person-organization fit toward affective commitment, (2) there was a direct effect of job satisfaction toward affective commitment, (3) there was a direct effect of trust toward affective commitment, (4) there was a direct effect of person-organization fit toward job satisfaction, (5) there was a direct effect of person-organization fit toward trust. the conclusion is that the affective commitment is influenced by the person-organization fit, job satisfaction and trust. Keywords: Affective commitment , person-organization fit, job satisfaction and trust